School Culture in High-Performance Title One Schools in South Texas - Padilla, George; Zamora, Roberto; Guerra, Jr., Federico (Journal of Leadership, Accountability and Ethics, 2020)
A research study was designed and conducted to identify effective school characteristics of four high-performing, high-poverty schools in South Texas. An eleven effective school characteristics model, including school processes, was developed based on a synthesis of effective school research and served as the theoretical framework for the study. The characteristics include Culture, Leadership, Instruction, Improvement, Home and Community Relations, Curriculum, Environment, Professional Development, Vision/Mission, Resources, and Staff. The mixed-research study collected and analyzed data from professional school staff, principals, and parents related to the schools' eleven effective characteristics and their processes. Results of the study supported the essentiality of the eleven school characteristics and identified Culture as an area of improvement. School staff perceived Culture’s essentiality for school effectiveness and its application in the schools relatively low. The schools’ cultural processes perceived by school staff and parents were very positive and consistent with past studies of effective schools. Caution is provided that high-performing schools may lose focus on Culture due to academic success.